2013
DOI: 10.1371/journal.pgen.1003647
|View full text |Cite
|
Sign up to set email alerts
|

Modification of tRNALysUUU by Elongator Is Essential for Efficient Translation of Stress mRNAs

Abstract: The Elongator complex, including the histone acetyl transferase Sin3/Elp3, was isolated as an RNA polymerase II-interacting complex, and cells deficient in Elongator subunits display transcriptional defects. However, it has also been shown that Elongator mediates the modification of some tRNAs, modulating translation efficiency. We show here that the fission yeast Sin3/Elp3 is important for oxidative stress survival. The stress transcriptional program, governed by the Sty1-Atf1-Pcr1 pathway, is affected in mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
153
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 122 publications
(158 citation statements)
references
References 61 publications
5
153
0
Order By: Relevance
“…The Elongator and Trm112 Complexes Are Revealed in the Genetic Screen-We recently reported that Elongator, a tRNA-modifying complex promoting efficient translation, was required for wild-type tolerance to peroxides (5). Indeed, our genetic screen also indicates that deletion of genes coding for different Elongator components express lower levels of basal or induced Ctt1-GFP (Table 2).…”
Section: Characterization Of a Reporter Of The Sty1-atf1mentioning
confidence: 69%
See 2 more Smart Citations
“…The Elongator and Trm112 Complexes Are Revealed in the Genetic Screen-We recently reported that Elongator, a tRNA-modifying complex promoting efficient translation, was required for wild-type tolerance to peroxides (5). Indeed, our genetic screen also indicates that deletion of genes coding for different Elongator components express lower levels of basal or induced Ctt1-GFP (Table 2).…”
Section: Characterization Of a Reporter Of The Sty1-atf1mentioning
confidence: 69%
“…Thus, we recently described that mutations in Elongator components impair wild-type tolerance to peroxides, probably by decreasing the amount of proteins synthesized from the stress mRNAs (5). Elongator introduces a modification of the anticodon loop of the low copy number tRNA UUU Lys as well as in other two types of tRNAs with a uracil 34 (U 34 ) in the 5Ј position of the anticodon (6,7).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We recently reported that the activity of this complex was required for proper tolerance to H 2 O 2 stress and that this effect was mediated by enhanced translation of the transcription factor Atf1. 19 From the 6 subunits of the Elongator complex, only Delp2 and Delp5 had wild type YFP/FSC ratios, with Diki3/Delp1 and Delp4 having the lowest YFP/FSC ratios (0.52) of all the strains that we tested from the knock-out collection, even below the strain lacking the known MBF co-activator Rep2 (0.55) (Fig. 3E and Table 1).…”
Section: Trna Methylation and Elongator Mutants Have Impaired Mbf-depmentioning
confidence: 86%
“…This fact was not completely surprising, since Trm112 dimerizes with another protein (either Trm9 or Mtq2) to form an active methylase that modifies specific nucleotides in tRNAs. 19 However, and despite these strains displaying decreased MBF activity (measured with the reporter strain or as the level of cdc18 transcript), none of these mutants were sensitive to hydroxyurea (HU) (Fig. 3C).…”
Section: Trna Methylation and Elongator Mutants Have Impaired Mbf-depmentioning
confidence: 99%